A Testis-Specific Long Noncoding RNA, Start, Is a Regulator of Steroidogenesis in Mouse Leydig Cells - Otsuka, Kai; Matsubara, Shin; Shiraishi, Akira; Takei, Natsumi; Satoh, Yui; Terao, Miho; Takada, Shuji; Kotani, Tomoya; Satake, Honoo; Kimura, Atsushi P. (Frontiers in Endocrinology, 2021)
The testis expresses many long noncoding RNAs (lncRNAs), but their functions and overview of lncRNA variety are not well understood. The mouse Prss/Tessp locus contains six serine protease genes and two lncRNAs that have been suggested to play important roles in spermatogenesis. Here, we found a novel testis-specific lncRNA, Start (Steroidogenesis activating lncRNA in testis), in this locus. Start is 1822 nucleotides in length and was found to be localized mostly in the cytosol of germ cells and Leydig cells, although nuclear localization was also observed. Start-knockout (KO) mice generated by the CRISPR/Cas9 system were fertile and showed no morphological abnormality in adults. However, in adult Start-KO testes, RNA-seq and qRT-PCR analyses revealed an increase in the expression of steroidogenic genes such as Star and Hsd3b1, while ELISA analysis revealed that the testosterone levels in serum and testis were significantly low. Interestingly, at 8 days postpartum, both steroidogenic gene expression and testosterone level were decreased in Start-KO mice. Since overexpression of Start in two Leydig-derived cell lines resulted in elevation of the expression of steroidogenic genes including Star and Hsd3b1, Start is likely to be involved in their upregulation. The increase in expression of steroidogenic genes in adult Start-KO testes might be caused by a secondary effect via the androgen receptor autocrine pathway or the hypothalamus-pituitary-gonadal axis. Additionally, we observed a reduced number of Leydig cells at 8 days postpartum. Collectively, our results strongly suggest that Start is a regulator of steroidogenesis in Leydig cells. The current study provides an insight into the overall picture of the function of testis lncRNAs.